Association of XRCC1 gene polymorphisms with susceptibility to gastric cancer in Chinese Han population. (29th April 2014) - Meng, Hua; Lu, Shuming; Zhang, Zhuqing; Chen, Meiru; Li, Chunyan; Liu, Lina; Luan, Yong
Abstract: Objectives: Gastric cancer is one of the most frequently causing cancer-related deaths worldwide. The X-ray repair complementing group 1 gene ( XRCC1 ) is an important candidate gene for influencing gastric cancer risk. This study aimed to evaluate the associations between XRCC1 genetic variants and gastric cancer susceptibility in Chinese Han population. Methods: Four hundred twenty-four gastric cancer patients and 430 cancer-free controls were enrolled. Two genetic variants (c.1254C>T and c.1779C>G) of XRCC1 gene were genotyped by created restriction site-polymerase chain reaction (PCR) and PCR-restriction fragment length polymorphism methods, respectively. Key findings: Results from this study indicated that the allele and genotype frequencies of these two genetic variants were statistically different between gastric cancer patients and cancer-free controls. The association analyses suggested that these two genetic variants were statistically associated with the increased risk of gastric cancer (for c.1254C>T, T versus C: odds ratio (OR) = 1.44, 95% confidence interval (CI) 1.17–1.77; for c.1779C>G, G versus C: OR = 1.51, 95% CI 1.22–1.86). The allele-T of c.1254C>T and allele-G c.1779C>G genetic variants may contribute to the susceptibility to gastric cancer in Chinese Han population. Conclusion: Our data suggest that these two genetic variants might be used as molecular markers for evaluating the susceptibility to gastric cancer.